1997
DOI: 10.3168/jds.s0022-0302(97)75941-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cefquinome for Treatment of Cows with Mastitis Experimentally Induced Using Escherichia coli

Abstract: The efficacy of intramuscularly and intramammarily administered cefquinome was evaluated in experimental Escherichia coli mastitis in dairy cows. Forty-seven multiparous, Israeli Holstein cows in early lactation that produced at least 25 L/d of milk were used, and 400 to 750 cfu of E. coli were infused into two healthy quarters of each cow. Cows were randomly assigned to one of the following treatment groups: 1) 75 mg of cefquinome administered intramammarily three times at 12-h intervals, 2) 75 mg of cefquino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
1
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 19 publications
1
53
1
4
Order By: Relevance
“…Our results clearly demonstrated that cows receiving MIR had higher cure rates than those receiving SAA alone. These results show that MIR is more effective than suggested by previous studies, which reported the beneficial effects of systemic antibacterial therapy in cows afflicted with coliform mastitis [8,19].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Our results clearly demonstrated that cows receiving MIR had higher cure rates than those receiving SAA alone. These results show that MIR is more effective than suggested by previous studies, which reported the beneficial effects of systemic antibacterial therapy in cows afflicted with coliform mastitis [8,19].…”
Section: Discussioncontrasting
confidence: 54%
“…Similarly, in the case of cows undergoing treatment for clinical coliform mastitis caused by gram-negative bacteria, there are reports on the possibility that antibiotic therapy can increase morbidity and mortality, which may be attributed to the release of endotoxins [4]. Therefore, although systemic antibacterial therapy may favorably influence the outcome of this disease in many cases [8,19], inappropriate choice of antibiotics may increase mortality due to the release of a large amount of endotoxins [14,20].…”
mentioning
confidence: 99%
“…A significant enhancement of activity and an extension of the antibacterial spectrum were achieved by the introduction of a methoxyimino-aminothiazolyl moiety into the acyl side chain of the cephalosporin, which made it resistant to inactivation by b-lactamases [6][7][8][9][10][11]. The quaternary quinoline group at position 3 in the cefem ring and the resulting zwitterionic structure facilitate the rapid penetration of cefquinome across the biological membranes of animals and bacteria, ensuring its fast bactericidal action after injection.…”
Section: Introductionmentioning
confidence: 99%
“…It is also active against many strains of methicillinresistant staphylococci and enterococci. Cefquinome sulfate is often applied in the treatment of meningitis-mastitis-agalactie (MMA) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of effective measures for prevention and control of the disease has markedly reduced subclinical and clinical mastitis [9]. However, there is still a great need for effective therapeutic measures against mastitis, although various preventive measures and management practices are effective.…”
mentioning
confidence: 99%